Familias, comunidad y escuela en el contexto de la cogestión educativa rural (Praxis Educativa, 2025)
We present an analysis of two instances convened by an alternating educational centre to develop projects together with the rural community, aimed at improving the quality of life of rural families. In this context, we analyse the dynamics of these spaces by identifying the problems, tensions and positions assumed by the various actors involved. Methodologically, we carried out a categorical analysis of audio transcripts generated from the participant observation carried out in these spaces of participation. We conclude that in these Educational Centres, families are assigned an active role in relation to the possibilities of creating strategies to improve their quality of life. At the same time, we observed a high degree of complexity in building consensus among the various actors who participate in these spaces.
Keywords: Rural education; Educational co-management; Community; Families; Participation